Rheological and mechanical properties of a novel polyamide 6 synthesized by anionic polymerization of ε-caprolactam in a twin-screw extruder. (26th August 2019) - Kim, Hoyeon; Oh, Kyunghwan; Seo, Yongsok
Abstract: In this study, we successfully synthesized a novel polyamide 6 (PA6, nylon 6) with a linking agent (a diepoxide) by in-situ reactive extrusion. In order to vary the physical properties of the polymer, a unique strategy was introduced. The linking agent reacted with growing PA6 chains during the anionic polymerization in the extruder. The extrudates appear to have a different structure (chain branching) without forming a network structure, causing a remarkable enhancement in the rheological properties as well as the mechanical properties of the nylon 6 produced. The molar ratio of linking agent to initiator was optimal at 0.1 and the produced polymers exhibit remarkably enhanced physical properties, though their molar masses was not appreciably varied. The melt viscosity of the produced PA6 including the optimum linking agent increased by almost 200 times that of the neat PA6 melt at low shear rate. The dynamic moduli also increased by more than 100 times that of the neat nylon 6. In addition, the mechanical properties were significantly improved with the addition of the linking agent. The elongation at break was almost doubled compared to neat PA6. The optimum compound showed a high toughness behavior. Graphical abstract: Image 1062 Highlights: A novel polyamide 6 (PA6, nylon 6) with a linking agent (a diepoxide) was successfully synthesized by in-situ reactive extrusion method. The linking agent reacted with growing PA6 chains during the anionic polymerization in the extruder. The melt viscosity of the PA6 with the optimum linking agent increased almost 200 fold at low shear rate.